SECURITIZATION AS A MAIN INSTRUMENT OF STRUCTURED FINANCE FOR BANKS: THEORETICAL BASIS AND LATEST TENDENCIES - V. Kyrii (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
In the article theoretical basis of securitization process was considered as main instrument for banks structured finance. Also features for main instruments of securitization were provided. The latest tendencies on securitization market in USA and Europe were analyzed.